Meningkatkan Kemampuan Motorik Kasar Anak Melalui Permainan Tradisional Paman Doli di RA Al-Ikhlas - Humairah, Rahma; Sitorus, Ahmad Syukri (WISDOM: Jurnal Pendidikan Anak Usia Dini, 2023)
This research is a classroom action research given to early childhood group B at RA Al Ikhlas Marindal, Patumbak District, Deli Serdang Regency, North Sumatra Province. This study aims to improve gross motor skills of children aged 5 to 6 years at RA Al Ikhlas Marindal through the traditional Uncle Doli’s traditional game. The subjects in this study were 12 children consisting of 7 girls and 5 boys in group B at RA Al Ikhlas Marindal. This classroom action research was conducted in 2 research cycles. The results of the research conducted obtained the results of the pre-cycle average value of 61.6, whereas in cycle 1 it was 65.8 and in cycle 2 it was 95.8. The results of this study indicate that the Uncle Doli's traditional games significantly improves gross motor skills of early childhood at RA Al Ikhlas Marindal.